Biotechnology and the agricultural industry : current status and prospects for research and development in biotechnology - Germany (West).; Technical Centre for Agricultural and Rural Cooperation (Ede, Netherlands) (Münster-Hiltrup [W. Germany] : Landwirtschaftsverlag, 1986)
The publication provides a broad overview of the present status of biotechnology and genetic engineering, their application and potential, as well as the goals and possibilities of the FMF in implementing a research and development-oriented strategy in the food and agricultural area
Translation of: Biotechnologie und Agrarwirtschaft: Stand und Perspektiven biotechnologischer Forschung und Entwicklung.
osc 29/01/2019
Loans
Keywords: Agricultural biotechnology; Biotechnology